Urinary Tract Infections in the First 6 Months after Renal Transplantation - Ziad Arabi; Khalefa Al Thiab; Abdulrahman Altheaby; Ghaleb Aboalsamh; Samy Kashkoush; Mohamad Almarastani; Mohammed F. Shaheen; Abdulrahman Altamimi; Wael O’hali; Khalid Bin Saad; Lina Alnajjar; Rawan Alhussein; et al. (International Journal of Nephrology)
Purpose. Urinary tract infections (UTIs) are common in the first 6 months after renal transplantation, and there are only limited data about UTIs after transplantation in Saudi Arabia in general. Methods. A retrospective study from January 2017 to May 2020 with 6-month follow-up. Results. 279 renal transplant recipients were included. Mean age was 43.4 ± 16.0 years, and114 (40.9%) were women. Urinary stents were inserted routinely during transplantation and were removed 35.3 ± 28 days postoperatively. Ninety-seven patients (35%) developed urinary tract infections (UTIs) in the first six months after renal transplantation. Of those who developed the first episode of UTI, the recurrence rates were 57%, 27%, and 14% for having one, two, or three recurrences, respectively. Late urinary stent removals, defined as more than 21 days postoperatively, tended to have more UTIs (OR: 1.43, P: 0.259, CI: 0.76–2.66). Age >40, female gender, history of neurogenic bladder, and transplantation abroad were statistically significant factors associated with UTIs and recurrence. Diabetes, level of immunosuppression, deceased donor renal transplantation, pretransplant residual urine volume, or history of vesicoureteral reflux (VUR) was not associated with a higher incidence of UTIs. UTIs were asymptomatic in 60% but complicated with bacteremia in 6% of the cases. Multidrug resistant organisms (MDROs) were the causative organisms in 42% of cases, and in-hospital treatment was required in about 50% of cases. Norfloxacin + Bactrim DD (160/800 mg) every other day was not associated with the lower risk of developing UTIs compared to the standard prophylaxis daily Bactrim SS (80/400 mg). Conclusion. UTIs and recurrence are common in the first 6 months after renal transplantation. Age >40, female gender, neurogenic bladder, and transplantation abroad are associated with the increased risk of UTIs and recurrence. MDROs are common causative organisms, and hospitalization is frequently required. Dual prophylactic antibiotics did not seem to be advantageous over the standard daily Bactrim.